Students’ perceptions of long-functioning cooperative teams in accelerated adult degree programs - Favor, Judy K. (My University, 2013)
This study examined 718 adult students’ perceptions of long-functioning cooperative study teams in accelerated associate’s, bachelors, and master’s business degree programs. Six factors were examined: attraction toward team, alignment of performance expectations, intra-team conflict, workload sharing, preference for teamwork, and impact on learning. Across degree programs, 66 - 71% of students reported equal work load sharing in their teams; 51 - 61% preferred teamwork; and 56 - 62% believed being on a team enhanced their learning. Significant statistical differences were found between associate degree and master’s degree students in performance expectation alignment, intra-team conflict, and teamwork preference.
Keywords: Adult education; Cooperative teams; Cooperative learning; Work load distribution; Accelerated programs